Chitty culinary traditions in Melaka, Malaysia. - Abd Ghani, Che Ann; Abdul Karim, Muhammad Shahrim (2011)
The article offers information about the culinary traditions of Chitty in Melaka, Malaysia. It mentions that the Chitty are also called Peranakan Indians, thus describing their origin, in the same way as the phrase is used to determine Peranakan Chinese. Moreover, modern Chitty continue to practice Hinduism, although the Chitty women can be easily determined from Indian women by their Nyonya or Malay dress.